Evaluation of Corneal Higher- Order Aberrations in Adults with Different Refractive Status - Yaseer, Omar Khaled; Darwish, Taym; Kurdogly, Najwa (Journal of medical and pharmaceutical sciences, 2021)
Purpose: The aim of this study is to evaluate the root mean square error (RMS) of corneal higher- order aberrations in Syrian adult population in different refractive status (emmetropia, myopia, hyperopia and simple myopic astigmatism). Methods: This cross- sectional study was conducted at Tishreen University Hospital in Latakia, Syrian Arab Republic. A total of 420 patients (840 eyes), ages 18- 40 years, participated in the study. Refraction was measured with an autorefractor keratometer and expressed as a spherical equivalent. Total corneal higher- order aberrations (Coma, Spherical Aberration, Trefoil) were measured using Sirius Corneal Topography at a pupil diameter of 5 mm. Results: RMS of Coma and Spherical aberrations peaked in the hyperopia group (0.18 ± 0.08, 0.11 ± 0.02) respectively. Whereas, Trefoil was higher in the severe myopia and simple myopic astigmatism groups (0.25 ± 0.05, 0.25 ± 0.08) respectively. Conclusions: Among a Syrian population, some types of refractive status were associated with certain types of higher- order aberrations, with a significant increase in trefoil in severe myopia and simple myopic astigmatism.